Film Dokumenter Penenun Tapis Lampung Sebagai Media Identitas Kultural - PG. Wisnu Wijaya (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2019)
The Lampung Wastra, called the Tapis, is an intangible artifact that has exotic characteristics and uniqueness like fabrics in other parts of Indonesia. All typical fabrics in the archipelago become cultural icons in each region, especially the Tapis discussed in this paper are indeed in the 'critical' space. In fact, the number of Tapis weavers and the process of regeneration of weavers is not going well. In fact, the number of Tapis weavers and the process of regeneration of weavers is not going well. Weavers who understand the history of Tapis, the meaning of motifs, patterns, types as well as their functions remain one person in Lampung, the rest only have an understanding in the aesthetic area and do not understand the deeper layers of the Tapis, both the meaning, historical value, articulation of forms and motifs used in the Tapis . The design of this documentary film will be made by combining direct cinema and social reconstruction documentary, referring to the form of direct cinema which is the disclosure of a fact that occurs about this Tapis fabric. polemic that occurs in the development of Tapis cloth in terms of philosophical, function and economic aspects, which will provide a strong dramatization in this documentary. For this reason, efforts should be made to build the image of Tapis fabric as a distinctive identity of Lampung cloth, build brand personality through weavers who still preserve cultural processes in making Tapis fabrics. Along with that there must be an effort to re-inform the philosophical values contained in the process of making Tapis fabric.